Assessing students' perceptions and preferences for Blackboard at a South African public university - Dominique Emmanuel Uwizeyimana; Victor H. Mlambo; Tasneem Majam; Carmen Joel (Association for Learning Technology, 2024)
This study examines students' perceptions and preferences for Blackboard at a South African public university. When the South African government, driven by COVID-19, announced the closure of schools in March 2020 for high school learners, home-schooling became the only option despite challenges such as lack of internet access, family support and computer access. This paper argued that learners were not prepared for home-schooling, which would negatively affect those in rural areas. It would be worse when they enrol for higher education as most universities in SA had adopted online learning. A quantitative research approach was used, and a sample of 370 first-year students was selected. The result showed that most first years found Blackboard easy and very easy to use. Moreover, the results show that despite this, some students preferred face-to-face learning more than Blackboard. This suggests that whilst Blackboard had its appeal, students still found comfort in familiar learning systems, especially considering that they had used such systems for most of their learning lives.